2010
DOI: 10.1186/1743-422x-7-318
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of core gene of HCV 3a genotype using synthetic and vector derived siRNAs

Abstract: BackgroundHepatitis C virus (HCV) is a major causative agent of liver associated diseases throughout the world, with genotype 3a responsible for most of the cases in Pakistan. Due to the limited efficiency of current therapy, RNA interference (RNAi) a novel regulatory and powerful silencing approach for molecular therapeutics through a sequence-specific RNA degradation process represents an alternative option.ResultsThe current study was purposed to assess and explore the possibility of RNAi to silence the HCV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 55 publications
1
27
0
Order By: Relevance
“…Taken advantage of the newly developed cell culture system of HCV infection in liver cells [27,28,41], the effect of siRNAs against whole virus was evaluated by treating cells with siRNA. Huh-7 serum infected cells were treated with 5'UTR siRNAs and subsequently incubated for 3 days.…”
Section: Resultsmentioning
confidence: 99%
“…Taken advantage of the newly developed cell culture system of HCV infection in liver cells [27,28,41], the effect of siRNAs against whole virus was evaluated by treating cells with siRNA. Huh-7 serum infected cells were treated with 5'UTR siRNAs and subsequently incubated for 3 days.…”
Section: Resultsmentioning
confidence: 99%
“…The nucleotide sequence homology analysis indicates the HCV isolates in this study (FR851292) belong to HCV core gene like Japan (D14309) and USA (EU099417). Previously this type of HCV was already isolated from this region [15]. This gives the idea that for endemic HCV this ELISA based kit method is much better because of local recombinant protein [16].…”
Section: Resultsmentioning
confidence: 99%
“…As replication occurs in the cytoplasm of liver cells without integration into the host genome DNA, HCV has emerged as a target of RNAi (40). Certain in vivo and in vitro experiments have demonstrated that exogenously administered short-interfering RNAs are able to exert replication inhibition against a variety of viruses (41)(42)(43)(44). In the present study, two sets of amiRNA expression vectors were designed and constructed against HCV1b genotype core and NS4B mRNAs, and it was investigated whether these amiRNAs were capable of efficiently inhibiting the expression of the HCV core and NS4B genes.…”
Section: Discussionmentioning
confidence: 99%